Spinel supported low-palladium catalyst as well as preparation method and application thereof
By loading low-content palladium on spinel support to regulate the interaction between the support and palladium, the problem of high cost and insufficient low-temperature activity in methane oxidation is solved, and high-efficiency, low-cost and stable catalytic effects are achieved, which are suitable for environmentally friendly and green catalytic applications.
Patent Information
- Application Number
- CN202510139885.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-29
AI Technical Summary
The existing palladium-based catalysts have high cost, insufficient low-temperature activity, poor stability, easy poisoning and environmentally friendly problems in methane oxidation.
Using a low-content palladium catalyst supported by biactive metal spinel, a high-efficiency, low-cost catalyst with excellent low-temperature activity and stability is prepared by regulating the composition of the support and the palladium loading process.
It realizes efficient methane oxidation of low-load palladium catalysts, reduces production costs, improves low-temperature catalytic performance and stability, and is suitable for low-temperature window catalytic environments, meeting the needs of energy-saving, environmentally friendly and green catalytic.
Smart Images

Figure CN119897087A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental catalysis technology, and in particular to a spinel-supported low-palladium catalyst and a preparation method and application thereof. Background Art
[0002] Methane is an important greenhouse gas with a greenhouse effect 23 times that of carbon dioxide. Compared with its resource recovery, complete catalytic oxidation is the cleanest and most effective method for methane control. Palladium-based catalysts show good catalytic performance in methane oxidation. Palladium presents different oxidation states during the catalytic process. 2+ It has a high electron affinity and can further drive the catalytic cycle; at the same time, the d-orbital electrons of palladium form coordination bonds with the orbits of methane molecules to achieve adsorption and activation of reactants. However, the application of precious metal palladium also has the following limitations: 1) high cost and resource scarcity; 2) insufficient interaction between the carrier and palladium; 3) active temperature window limitation; 4) catalyst deactivation and poisoning problems; 5) environmental friendliness issues. In view of the above problems, optimization is still needed from the perspective of material design, preparation process and reaction mechanism research. Figure 2 This is a summary of the performance of different palladium-based catalysts in the catalytic oxidation of methane reported in the literature. In the prior art, high-loaded palladium is usually used, which not only increases the cost of the catalyst, but also makes its low-temperature activity and long-term stability become limiting factors. Summary of the invention
[0003] The purpose of the present invention is to solve the above problems in the prior art and to provide a spinel-supported low-palladium catalyst and a preparation method and application thereof.
[0004] The first purpose of the present invention is to provide a dual-active metal spinel-loaded low-content palladium-based catalyst and a preparation method thereof. By regulating the composition of the carrier and the palladium loading process, a high-efficiency, low-cost catalyst with excellent low-temperature activity and stability is prepared to achieve efficient and complete catalytic oxidation of methane and promote the clean combustion application of methane in natural gas.
[0005] The second purpose of the present invention is to maximize the catalytic activity and stability of the precious metals, reduce the use of precious metals, and reduce the cost of the catalyst by designing and regulating the transition metals (such as nickel and cobalt) with various valence states in the octahedral sites of the dual-active metal spinel carrier and utilizing the metal-carrier interaction relationship between the carrier and the precious metals.
[0006] The third object of the present invention is to provide an efficient and economical method for preparing a catalyst, optimize the loading amount and dispersion of palladium, and provide a universal regulation method for the synthesis and application of low-content precious metal-based catalysts.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A spinel-supported low-palladium catalyst composed of nano-particles of ZnNi 0.6 Co 1.4 O 4 The spinel is used as an active support and the surface active centers are formed by palladium impregnation loading; ZnNi 0.6 Co 1.4 O 4 The octahedral sites of the spinel carrier are occupied by active bimetallic Ni and Co, and Zn is fixed at the tetrahedral sites of the spinel carrier; the loading amount of palladium is 0.3% to 1.5%, and more preferably, the loading amount of palladium is 0.5%.
[0009] The octahedral sites of the spinel carrier of the catalyst are occupied by active bimetallic catalysts, and the synergistic interaction with the surface noble metal palladium can maximize the catalytic activity of the noble metal, reduce the amount of noble metal used, and reduce the cost of the catalyst. The synthesis of the present invention fixes the catalytically inactive Zn at the tetrahedral sites of the spinel carrier, and the multivalent active bimetallic Ni and Co occupy the octahedral sites. The interaction between the transition metals provides different anchoring environments for palladium, and the 0.5Pd / ZnNi catalyst with excellent catalytic activity is obtained through the interaction between the carrier and palladium. 0.6 Co 1.4 O 4 catalyst.
[0010] The method for preparing a spinel-supported low-palladium catalyst comprises the following steps:
[0011] 1) Dissolve zinc salt, nickel salt and cobalt salt in dilute nitric acid in a molar ratio of 1:0.6:1.4 and stir to form a uniform solution;
[0012] 2) The above solution is evaporated and then transferred to an oven for aging. The obtained solid is ground and calcined to obtain ZnNi 0.6 Co 1.4 O 4 Spinel carrier;
[0013] 3) Palladium nitrate and ZnNi 0.6 Co 1.4 O 4 The carrier is dissolved in ultrapure water, stirred, ultrasonicated, evaporated, dried, ground and calcined to obtain the spinel-supported low-palladium catalyst.
[0014] The zinc salt, nickel salt and cobalt salt are any one of nitrate and acetate.
[0015] In step 2), the aging temperature is 120~180°C and the aging time is 12~16 h.
[0016] In step 2), the calcination conditions are 400-600 °C for 4-8 h.
[0017] In step 3), the calcination conditions are 400-600 °C for 4-8 h.
[0018] The application of the spinel-supported low-palladium catalyst is used for catalytic oxidation of methane; the specific process of the application of the catalyst in catalytic oxidation of methane is as follows: 100-500 mg of the catalyst is mixed with quartz sand and loaded into a microreactor, and the inlet gas (1 vol% methane, air balance) is introduced at a flow rate of 50-200 mL / min. An online gas chromatograph equipped with an FID detector measures the outlet gas flow composition within the test temperature range to evaluate the catalyst performance.
[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0020] 1. Low cost and high efficiency: The catalyst of the present invention has a low content of precious metals (0.5%) and is based on the abundant and inexpensive transition metal spinel ZnNi 0.6 Co 1.4 O 4 As a carrier, the synthesis process is simple, which effectively reduces the production cost of the catalyst. Compared with high-load palladium-based catalysts, the present invention can not only maintain a considerable catalytic activity, but also significantly reduce the amount of precious metal palladium used, solving the cost problem of precious metals.
[0021] 2. Excellent low-temperature catalytic performance: The catalyst has significant low-temperature catalytic activity. In the methane catalytic oxidation reaction, the catalyst can achieve a methane conversion rate of 90% at around 350°C, which is much lower than the reaction temperature of traditional catalysts. This makes the catalyst of the present invention suitable for low-temperature window catalytic environment, which can greatly improve the methane conversion rate while reducing energy consumption.
[0022] 3. Enhanced catalyst stability: The catalyst of the present invention exhibits high stability during long-term reactions. In the catalytic oxidation reaction of methane, the catalyst can maintain high catalytic activity under high temperature and long-term reaction conditions without significant failure; and the thermogravimetric results show that the catalyst still maintains less carbon deposition after long-term operation and has good anti-poisoning ability. This feature makes the catalyst suitable for practical industrial applications.
[0023] 4. Synergistic effect of bimetallic spinel carrier: The present invention innovatively introduces cheap transition metals nickel and cobalt with multivalent states into the main active site of spinel - the octahedral site, which exhibits good synergistic effect with surface precious metals during the catalytic process. The interaction between transition metals provides different anchoring environments for palladium, improving the stability and catalytic activity of palladium. This regulation strategy not only improves the low-temperature activity of the catalyst, but also improves the anti-toxicity and long-term stability of the catalyst.
[0024] 5. High-efficiency methane catalytic oxidation performance: In the experiment, when the catalyst of the present invention is used for methane catalytic oxidation reaction ( ), the catalyst can quickly achieve complete oxidation of methane and maintain a high reaction rate at a low temperature. Especially in the case of low palladium loading, the catalyst exhibits excellent performance and long service life, meeting environmental protection requirements and in line with the application trend of green chemistry.
[0025] In summary, the low-loaded palladium-based catalyst of the present invention not only reduces the production cost, but also greatly improves the low-temperature performance and catalytic stability. It is particularly suitable for methane catalytic oxidation reaction and meets the actual needs of energy conservation, environmental protection and green catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are the performance test results of palladium-based catalysts with different molar ratios of carriers in the complete catalytic oxidation of methane.
[0027] Figure 2 The performance of different palladium-based catalysts reported in the literature for the complete catalytic oxidation of methane is summarized.
[0028] Figure 3 Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of the prepared catalysts show the particle size and morphology of the catalysts.
[0029] Figure 4 X-ray diffraction (XRD) spectra and nitrogen adsorption-desorption (S BET ) curve to verify the crystal and pore structure of the catalyst.
[0030] Figure 5 This is the high-resolution transmission electron microscopy (EDS mapping) energy spectrum of the prepared catalyst, which shows the uniform distribution of each element in the catalyst, especially the precious metal palladium is in a dispersed state without agglomeration.
[0031] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) diagram of the prepared catalyst, which analyzes the chemical state of the elements on the catalyst surface.
[0032] Figure 7This is a graph showing the relationship between the conversion rate and temperature of catalysts with different precious metal loadings for catalytic oxidation of methane.
[0033] Figure 8 This is a graph showing the relationship between the conversion rate and temperature of the prepared catalyst for methane catalytic oxidation reaction.
[0034] Fig. 9 These are the test results of thermal stability and water vapor stability of the prepared catalyst.
[0035] Fig.10 This is the SEM image of the prepared catalyst after hydrothermal stability test.
[0036] Fig.11 These are the XRD and thermogravimetric (TGA) test results of the prepared catalyst after hydrothermal stability test. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0038] Example 1
[0039] This example illustrates that 0.5Pd / ZnNi 0.6 Co 1.4 O 4 Catalyst preparation and morphological characterization (SEM, TEM, XRD, S BET , XPS); where 0.5 means that the Pd loading is 0.5%.
[0040] 1. ZnNi 0.6 Co 1.4 O 4 Preparation of catalyst carrier:
[0041] Step 1: Dissolve the solid particles of zinc salt, nickel salt and cobalt salt in the required ratio (molar ratio of 1:0.6:1.4) in an appropriate amount of dilute nitric acid and stir to form a uniform solution; this molar ratio is the preferred value (see Figure 1 ); The required dilute nitric acid is a solution of water and concentrated nitric acid in a volume ratio of 1:10;
[0042] Step 2: The above solution was evaporated to remove most of the water, transferred to an oven and aged overnight at 170 °C, the solid material was ground to obtain a black powder, calcined in a muffle furnace at 500 °C for 6 h, and the black solid obtained after cooling was ground to obtain the carrier material ZnNi 0.6 Co 1.4 O 4 .
[0043] 2. 0.5Pd / ZnNi0.6 Co 1.4 O 4 Preparation of catalyst:
[0044] Step 1: Add an appropriate amount of palladium nitrate and the ZnNi 0.6 Co 1.4 O 4 The carrier (the mass ratio of palladium to carrier is 1:200) was dissolved in ultrapure water, evaporated to remove water after ultrasonic and stirring dispersion, and transferred to an oven to dry overnight at 170 °C. The solid material was ground to obtain a black powder, which was calcined at 500 °C in a muffle furnace for 6 h. After cooling, the final 0.5Pd / ZnNi 0.6 Co 1.4 O 4 catalyst.
[0045] The 0.5Pd / ZnNi obtained in this example 0.6 Co 1.4 O 4 Catalyst morphology and structure characterization (SEM, TEM, XRD, S BET , XPS):
[0046] The morphology and structure of the catalyst obtained above were characterized by SEM and TEM images ( Figure 3 ) shows that the catalyst particles are uniform, mainly irregular nanoparticle agglomerates, and the particle size is about 20 nm. XRD analysis ( Figure 4 ) confirmed that the catalyst exhibited a cubic spinel structure, no obvious palladium peak was found, and it was consistent with the EDS spectrum ( Figure 5 ) combined with the uniform distribution of Pd, Zn, Ni, Co and O in the catalyst, among which the distribution of the precious metal Pd is dispersed without obvious agglomeration. Nitrogen adsorption and desorption curve ( Figure 4 ) Analysis of 0.5Pd / ZnNi 0.6 Co 1.4 O 4 The specific surface area of the catalyst is 15.7 m 2 / g. XPS( Figure 6 ) Analysis shows that nickel on the catalyst surface mainly exists in trivalent form, cobalt exists in divalent form, and palladium mainly exists in divalent and tetravalent forms, and the ratio is close to 1. This characteristic is conducive to promoting the redox cycle of the catalyst during the reaction and increasing the reaction rate.
[0047] Example 2
[0048] This example illustrates the preparation of catalysts with different palladium loadings and the performance comparison of this series of catalysts for the complete catalytic oxidation of methane.
[0049] 1. xPd / ZnNi 0.6 Co1.4 O 4 Preparation of catalysts, where x = 0.3, 0.5, 0.8, 1.0, 1.5, i.e., the Pd loadings are 0.3%, 0.5%, 0.8%, 1.0%, 1.5%, respectively;
[0050] Step 1: dissolving solid particles of zinc salt, nickel salt and cobalt salt in the required ratio (molar ratio of 1:0.6:1.4) in an appropriate amount of dilute nitric acid and stirring to form a uniform solution; this molar ratio is a preferred value;
[0051] Step 2: The above solution was evaporated to remove most of the water, transferred to an oven and dried overnight at 170 °C, the solid material was ground to obtain a black powder, calcined in a muffle furnace at 500 °C for 6 h, and the black powder was ground after cooling to obtain the carrier material ZnNi 0.6 Co 1.4 O 4 .
[0052] Step 3: Add an appropriate amount of palladium nitrate and the ZnNi 0.6 Co 1.4 O 4 The carrier (the mass ratio of palladium to carrier was 0.3%, 0.5%, 0.8%, 1.0%, and 1.5%, respectively) was dissolved in ultrapure water, evaporated to remove water after ultrasonic and stirring dispersion, and transferred to an oven to dry overnight at 170 °C. The obtained solid material was ground to obtain a black powder and calcined in a muffle furnace at 500 °C for 6 h. After cooling, the final xPd / ZnNi 0.6 Co 1.4 O 4 (x=0.3, 0.5, 0.8, 1.0, 1.5) catalyst.
[0053] 2. Performance test of catalysts with different palladium loadings for catalytic oxidation of methane:
[0054] The specific process of the application of the catalyst in the catalytic oxidation of methane is as follows: 200 mg of the catalyst was mixed with quartz sand and loaded into the microreactor, and the inlet gas (1 vol% methane, air balance) was introduced at a flow rate of 100 mL / min. The composition of the outlet gas flow within the test temperature range was measured by an online gas chromatograph equipped with an FID detector to evaluate the catalyst performance.
[0055] Through the above-mentioned online monitoring device, this example evaluates the performance of catalysts with different palladium loadings for catalytic oxidation of methane ( Figure 7), wherein the catalytic performance of the 0.5 wt% palladium-loaded catalyst is comparable to that of the 0.8 wt% palladium-loaded catalyst, and is superior to those of the 1.0 wt% and 1.5 wt% palladium-loaded catalysts, which is related to the precious metal dispersion results of the catalyst in Example 1.
[0056] Example 3
[0057] This example illustrates that 0.5Pd / ZnNi 0.6 Co 1.4 O 4 The catalyst was used to test the performance of catalytic oxidation of methane.
[0058] The specific process of the application of the catalyst in the catalytic oxidation of methane is as follows: 200 mg of the catalyst was mixed with quartz sand and loaded into a microreactor, and the inlet gas (1 vol% methane, air balance) was introduced at a flow rate of 100 mL / min. The online gas chromatograph equipped with an FID detector measured the composition of the outlet gas flow within the test temperature range to evaluate the catalyst performance. The test temperature range was 200~500 ℃.
[0059] Through the above-mentioned online monitoring device, this example evaluates the 0.5Pd / ZnNi 0.6 Co 1.4 O 4 Performance of catalysts for methane catalytic oxidation ( Figure 8 ), at 311 °C, the catalyst of the present invention showed a methane conversion rate of 50%, at 358 °C, 0.5Pd / ZnNi 0.6 Co 1.4 O 4 The catalyst has a conversion rate of 90% and exhibits excellent low-temperature catalytic performance, which exceeds the performance of different palladium-based catalysts reported in the literature in the past three years ( Figure 2 ).
[0060] Example 4
[0061] This example illustrates that 0.5Pd / ZnNi 0.6 Co 1.4 O 4 The catalyst was used for thermal and water vapor stability testing of catalytic methane oxidation.
[0062] The specific process of the thermal stability test of the catalyst in the catalytic oxidation of methane is as follows: an appropriate amount of catalyst is mixed with quartz sand and loaded into a microreactor, and an inlet gas (1 vol% methane, air balance) is introduced at a flow rate of 100 mL / min. An online gas chromatograph equipped with an FID detector measures the composition of the outlet gas flow within the test temperature range to evaluate the catalyst performance. The test temperature is fixed at 300 ℃ and 350 ℃.
[0063] The specific process of the water vapor stability test of the catalyst in the catalytic oxidation of methane is as follows: an appropriate amount of catalyst is mixed with quartz sand and loaded into a microreactor, and an inlet gas (1 vol% methane, 5 vol% water vapor, air balance) is introduced at a flow rate of 50 mL / min. An online gas chromatograph equipped with an FID detector measures the composition of the outlet gas flow within the test temperature range to evaluate the catalyst performance. The test temperature is fixed at 350 °C.
[0064] Through the above-mentioned online monitoring device, this example evaluates the 0.5Pd / ZnNi 0.6 Co 1.4 O 4 Stability of the catalyst for methane catalytic oxidation ( Fig. 9 ), thermal stability tests show that the catalyst of the present invention can maintain stable activity within 20 h. After adding 5 vol% water vapor, the methane conversion rate decreases from ~90% to ~70%, which is in line with the market's expectations for the water resistance of catalysts used for catalytic oxidation of methane.
[0065] Example 5
[0066] This example illustrates the 0.5Pd / ZnNi 0.6 Co 1.4 O 4 Catalyst morphology and structure characterization (XRD, SEM, TGA).
[0067] The catalyst obtained after the water vapor and thermal stability tests was subjected to morphological structure characterization and carbon deposition test. SEM images ( Fig.10 ) shows that the catalyst particles are uniform and remain as irregular nanoparticle agglomerates after stability testing. XRD analysis ( Fig.11 ) confirmed that the catalyst maintained a cubic spinel structure, and no obvious palladium peak appeared, confirming the structural stability of the catalyst and the good dispersion of Pd on the catalyst surface. Thermogravimetric analysis ( Fig.11 ) The carbon deposit content of the catalyst was tested.
[0068] In summary, the catalyst of the present invention can maintain excellent catalytic activity under high temperature and long-term reaction conditions in the methane catalytic oxidation reaction, and the thermogravimetric results show that the catalyst can maintain less carbon deposition after long-term operation, indicating that it has good anti-poisoning ability. This characteristic makes the catalyst suitable for practical industrial applications, can operate for a long time without significant failure, and shows excellent application prospects.
Claims
1. A spinel supported low-palladium catalyst, characterized in that: Nanoparticles of ZnNi 0.6 Co 1.4 O4 spinel as an active carrier, and the surface active centers formed by palladium impregnation loading; ZnNi 0.6 Co 1.4 The octahedral sites of the O4 spinel support are occupied by active bimetallic Ni and Co, and Zn is fixed on the tetrahedral sites of the spinel support; the palladium loading is 0.3%~1.5%.
2. A spinel supported low-palladium catalyst as claimed in claim 1, characterized in that: The palladium loading is 0.5%.
3. The preparation method of a spinel supported low-palladium catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) Dissolve zinc salt, nickel salt and cobalt salt in dilute nitric acid in a molar ratio of 1:0.6:1.4 and stir to form a uniform solution; 2) The above solution is evaporated and then transferred to an oven for aging. The obtained solid is ground and calcined to obtain ZnNi 0.6 Co 1.4 O4 spinel carrier; 3) Palladium nitrate and ZnNi 0.6 Co 1.4 The O4 carrier is dissolved in ultrapure water, stirred, ultrasonicated, evaporated, dried, ground, and calcined to obtain the spinel-supported low-palladium catalyst.
4. The preparation method according to claim 3, characterized in that: The zinc salt, nickel salt and cobalt salt are any one of nitrate and acetate.
5. The preparation method according to claim 3, characterized in that: In step 2), the aging temperature is 120~180°C, and the aging time is 12~16 h.
6. The preparation method according to claim 3, characterized in that: In step 2), the calcination conditions are 400-600 °C for 4-8 h.
7. The preparation method according to claim 3, characterized in that: In step 3), the calcination conditions are 400-600 °C for 4-8 h.
8. The use of a spinel supported low-palladium catalyst according to claim 1, characterized in that: Used for catalytic oxidation of methane.
9. The use of a spinel supported low-palladium catalyst prepared by any one of the preparation methods of claims 3 to 7, characterized in that: Used for catalytic oxidation of methane.